2016
DOI: 10.1017/s2045796016000962
|View full text |Cite
|
Sign up to set email alerts
|

The long-term mental health risk associated with non-heterosexual orientation

Abstract: Non-heterosexual orientation was not a major risk factor for long-term mental health outcomes. Instead, those with a non-heterosexual orientation were more likely to experience other mental health risk factors, which explain most of the risk observed amongst those with a non-heterosexual orientation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 32 publications
5
12
0
Order By: Relevance
“…The mediation was especially pronounced for boys 2. Burns et al ( 2016 ) Series of regressions A bisexual but not a homosexual orientation was found to predict increased rates of depression compared to those with a heterosexual orientation. This association was no longer significant when other significant predictors were included in the model, including social support, physical health, smoking status, and history of sexual trauma, suggesting the potential mediating role of these variables (although the authors did not describe these as mediators) 3.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The mediation was especially pronounced for boys 2. Burns et al ( 2016 ) Series of regressions A bisexual but not a homosexual orientation was found to predict increased rates of depression compared to those with a heterosexual orientation. This association was no longer significant when other significant predictors were included in the model, including social support, physical health, smoking status, and history of sexual trauma, suggesting the potential mediating role of these variables (although the authors did not describe these as mediators) 3.…”
Section: Resultsmentioning
confidence: 99%
“…Almeida et al ( 2009 ) 1 1 0 1 0 1 0 0 0 1 1 0 Fair 2. Burns et al ( 2016 ) 1 1 0 0 0 0 0 1 1 1 1 1 Fair 3. Burton et al ( 2013 ) 1 1 1 1 0 1 0 1 1 1 0 1 Good 4.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations